Exploring the integration of ideological values with artificial intelligence technology: A legal awareness perspective - Rejekiningsih, Triana; Hakimi, Hanan al (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Artificial Intelligence (AI) Technology has potential benefits and challenges that the law of awareness must overcome. Behavior contrary to legal norms often appears in AI, which can harm and endanger the nation's life. The low compliance and moral awareness of AI users that is not in line with Pancasila values has led to the emergence of various conflicts in society. This study aims to explore three aspects related to the use of AI. First, students' perceptions of the use of AI. Secondly, the use of AI technology based on Pancasila values; third, efforts to form legal awareness of the use of AI Technology. The study results show that almost all students know and have used AI technology, especially in academic activities. This research was conducted using qualitative methods and a case study approach. Data collection was carried out through observation, distribution of questionnaires, and interviews with 205 students of Sebelas Maret University as respondents. In addition, literature studies and interviews were also conducted with several key informants. Data processing uses the triangulation method, which uses interactive model data analysis from Miles & Huberman. To use AI wisely and follow Pancasila values, students must understand the ethics and laws of using this technology.